Pengaruh Olahraga Jalan Santai Terhadap Kadar Glukosa Darah Pada Pasien Diabetes Mellitus - Widiya, Arkan Adi, dr. Sigit Widyatmoko, Sp. PD, M. Kes, dr. Safari Wahyu Jatmiko (2015)
Background: Diabetes mellitus (DM) is a chronic disease that occurs because the pancreas cannot produce enough insulin or the body cannot effectively use the insulin that produced by the pancreas. There are 4 ways to maintain blood glucose levels, namely; pharmacological therapy, nutritional therapy, diabetes self-management education, and physical activity. Walking exercise is the most often described as the modalities of physical activity to improve health. Aim: Knowing the effects of walking exercise on blood glucose levels in patients with diabetes mellitus Methods: This study is an observational cross-sectional analytic approach. Samples of 68 people who participate in walking exercise in Prolanis Padimas Surakarta. Sampling was done by purposive sampling. Walking exercise activities carried out as far as 2 kilometers and takes about 30 minutes. Results: The results of different statistical tests glucose before and after walking exercise activities way using paired T test showed p<0.001, which indicates that a significant or meaningful results and have a correlation value is 0.963 which is shown to have a very strong influence. Conclusion: This study found that walking exercise as far as 2 km for 30 minutes can lower blood glucose levels significantly in patients with diabetes mellitus.